2016
DOI: 10.1080/10409238.2016.1215407
|View full text |Cite
|
Sign up to set email alerts
|

Exonuclease 1 and its versatile roles in DNA repair

Abstract: Exonuclease 1 (EXO1) is a multifunctional 5' → 3' exonuclease and a DNA structure-specific DNA endonuclease. EXO1 plays roles in DNA replication, DNA mismatch repair (MMR) and DNA double-stranded break repair (DSBR) in lower and higher eukaryotes and contributes to meiosis, immunoglobulin maturation, and micro-mediated end-joining in higher eukaryotes. In human cells, EXO1 is also thought to play a role in telomere maintenance. Mutations in the human EXO1 gene correlate with increased susceptibility to some ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 115 publications
2
52
0
Order By: Relevance
“…52, 53 Another important mediator, EXO1 is involved in cell cycle and MMR, which have a role in telomere maintenance and proliferative capacity of stem cells. 54 Our RT-PCR results verified the lower expression of CCNA2 , MCM6 , RAD21 , EXO1 and STAG1 in P3 BMSCs compared with BMMNCs, indicating that expansion may alter telomerase activity and chromosomal stability of MSCs, leading to impaired stemness and multipotency. Many studies have demonstrated absence of telomerase activity in human MSCs.…”
Section: Discussionsupporting
confidence: 74%
“…52, 53 Another important mediator, EXO1 is involved in cell cycle and MMR, which have a role in telomere maintenance and proliferative capacity of stem cells. 54 Our RT-PCR results verified the lower expression of CCNA2 , MCM6 , RAD21 , EXO1 and STAG1 in P3 BMSCs compared with BMMNCs, indicating that expansion may alter telomerase activity and chromosomal stability of MSCs, leading to impaired stemness and multipotency. Many studies have demonstrated absence of telomerase activity in human MSCs.…”
Section: Discussionsupporting
confidence: 74%
“…However, how resection is restrained or terminated is not well understood. Our results uncover a novel mechanism by which resection is negatively regulated via the degradation of EXO1, an exonuclease with critical functions in long-range resection (25,26). Our results indicate that EXO1, although vital for resection and HR, is rapidly degraded after DNA damage in a phosphorylation-and ubiquitination-dependent manner.…”
Section: Discussionmentioning
confidence: 72%
“…EXO1 is a 5Ј to 3Ј exonuclease with key roles in DNA mismatch repair, mitotic and meiotic recombination, replication, and telomere homeo-stasis (for review, see Refs. [25][26][27]. Research from our laboratory has established that EXO1 plays a major role in DNA end resection in human cells and not only promotes a switch from NHEJ to HR but also facilitates a transition from ATM-to ATRmediated checkpoint signaling (15,16,23,28,29).…”
mentioning
confidence: 99%
“…Exo1 promotes recombination by catalyzing 5´ to 3´ DNA strand resection (Keijzers et al, 2016), and its loss results in a ~2.5 fold reduction in gene conversions, and a ~2 fold reduction in deletions, in strains with RTS1 -AO and no additional DNA spacer (Figure 4A) (Osman et al, 2016). Its loss also causes a similar reduction in gene conversions (~2.2 fold) when the centromere-proximal 5 kb spacer is added (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%